First women : - Brower, Kate Andersen (Harper, an imprint of HarperCollins Publishers, 2016)
Brower draws on a wide array of untapped, candid sources to tell the stories of the ten remarkable women who have defined the role of First Lady of the United States since 1960. From Jackie Kennedy to Michelle Obama, she offers new insights into this privileged group, and shares stories exploring everything from the first ladies political crusades to their rivalries with Washington figures; from their friendships with other first ladies to their public and private relationships with their husbands..